Polemik Pengusulan Rancangan Undang-Undang Haluan Ideologi Pancasila (RUU HIP) - Ningsih Susilawati (UIN Mataram, 2020)
This article will discuss the polemic of the proposed Pancasila Ideology Bill (HIP Bill) which has recently been widely discussed by the public. There are several parts in to this bill that are contradictory and raise questions, considering that the concentration of this bill is the state's ideology. The values ??of Pancasila that are universal need to be translated specifically through the legislation and laws refer to the hierarchy of law in Indonesia, this basis is defined by the Legislative Body of the DPR to propose the HIP Bill. This paper use qualitative research method with descriptive analysis approach through the collection of related literature studies. The results of this study indicate that the purpose of the proposal, legal basis, as well as the content and content of the academic text of the HIP Bill is still unclear so caused debate and rejection from the society.